Kinetics of Vitamin A Degradation and Oxidation of Palm Oil Fortified with Retinyl Palmitate and ?-Carotene from Red Palm Oil - Krisna Margaretta Malau; Nuri Andarwulan; Drajat Martianto; Desty Gitapratiwi; Ayu Cahyaning Wulan; Dwi Fitriani; Purwiyatno Hariyadi (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Retinyl palmitate and ?-carotene from red palm oil (RPO-?-carotene) can be used as sources to fortify vegetable oil. The present study tested three types of bulk palm cooking oil with a peroxide value (PV) of 0, ±4, and ±8 mEq O2kg-1 which each was fortified with retinyl palmitate or RPO-?-carotene alone and combination of both fortificants. The stability of the fortificants in oil samples during storage was investigated. A kinetic analysis of oxidation reaction in fortified palm cooking oil stored in tightly closed amber vials in the dark at different temperatures (60±5, 75±5, and 90±5 °C) was conducted, and then PV, vitamin A concentration and their change rate of reaction in the oils were measured. It reveals that initial PV and mixture of retinyl palmitate and RPO-?-carotene in fortified oil affected the oil stability. Higher initial PV of oil increased the reaction rate constant of peroxide formation and degradation of vitamin A activity during storage. Oxidation reactions of oil samples fortified with the mixtures of retinyl palmitate and RPO-?-carotene was faster than that fortified with retinyl palmitate or RPO-?-carotene only. Our research suggests that applying single fortificant of retinyl palmitate or RPO-?-carotene in oil is more stable than that fortified with combination of both fortificants.